Taxonomic Revision of the Subfamily Sterculioideae Beilschm. In Bangladesh (Bangladesh Journal of Plant Taxonomy, 2022)
The subfamily Sterculioideae Beilschm. of Malvaceae has been revised for Bangladesh which revealed 16 taxa belonging to five genera, such as Firmiana Marsili, Heritiera Ait., Pterygota Schott & Endl., Scaphium Schott & Endl. and Sterculia L. The genus Sterculia is unveiled with the highest number of taxa, whereas both Pterygota and Scaphium are represented with single taxon. Dichotomous bracketed keys to genera and species are constructed for easy identification. Each taxon is presented with an updated nomenclature, description of the taxa along with illustrations, specimens examined, phenology, notes on distribution and economical importance. In most cases, chromosome number has been provided.Bangladesh J. Plant Taxon. 29(2): 373-401, 2022 (December)